Amorphous/crystalline heterostructured cobalt-vanadium-iron (Oxy)hydroxides for highly efficient oxygen evolution reaction - Kuang, Min (2022)
The oxygen evolution reaction (OER) is a key process involved in energy and environment-related technologies. An ideal OER electrocatalyst should show high exposure of active sites and optimal adsorption energies of oxygenated species. However, earth-abundant transition-metal-based OER electrocatalysts still operate with sluggish OER kinetics. Here, a cation-exchange route is reported to fabricate cobalt-vanadium-iron (oxy)hydroxide (CoV-Fe0.28) nanosheets with tunable binding energies for the oxygenated intermediates. The formation of an amorphous/crystalline heterostructure in the CoV-Fe0.28 catalyst boosts the exposure of active sites compared to their crystalline and amorphous counterparts. Furthermore, the synergetic interaction of Co, V, and Fe cations in the CoV-Fe0.28 catalyst subtly regulates the local coordination environment and electronic structure, resulting in the optimal thermodynamic barrier for this elementary reaction step. As a result, the CoV-Fe0.28 catalyst exhibits superior electrocatalytic activity toward the OER. A low overpotential of 215 mV is required to afford a current density of 10 mA cm−2 with a small Tafel slope of 39.1 mV dec−1, which outperforms commercial RuO2 (321 mV and 86.2 mV dec−1, respectively).